Both GPER and membrane oestrogen receptor‐α activation protect ventricular remodelling in 17β oestradiol‐treated ovariectomized infarcted rats. Issue 12 (25th September 2014) - Lee, Tsung‐Ming; Lin, Shinn‐Zong; Chang, Nen‐Chung
Abstract Clinical and experimental studies have established that gender is a factor in the development of ventricular hypertrophy. We investigated whether the attenuated hypertrophic effect of oestradiol was via activation of phosphatidylinositol 3‐kinase (PI3K)/Akt/endothelial nitric oxide synthase (eNOS) through non‐genomic action. Twenty‐four hours after coronary ligation, female Wistar rats were randomized into control, subcutaneous oestradiol treatment or a G‐protein coupled oestrogen receptor (GPER) agonist, G‐1 and treated for 4 weeks starting from 2 weeks after bilateral ovariectomy. Ventricular hypertrophy assessed by cardiomyocyte size after infarction was similarly attenuated by oestradiol or G‐1 in infarcted rats. The phosphorylation of Akt and eNOS was significantly decreased in infarcted rats and restored by oestradiol and G‐1, implying the GPER pathway in this process. Oestradiol‐induced Akt phosphorylation was not abrogated by G‐15 (a GPER blocker). Akt activation was not inhibited by actinomycin D. When a membrane‐impermeable oestrogen‐albumin construct was applied, similar responses in terms of eNOS activation to those of oestradiol were achieved. Furthermore, PPT, an ERα receptor agonist, activated the phosphorylation of Akt and eNOS. Thus, membrane ERα receptor played a role in mediating the phosphorylation of Akt and eNOS. The specific PI3K inhibitor, LY290042, completely abolished Akt activation and eNOS phosphorylation in infarcted hearts treated with either oestradiol or oestradiol + G‐15. These data support the conclusions that oestradiol improves ventricular remodelling by both GPER‐ and membrane‐bound ERα‐dependent mechanisms that converge into the PI3K/Akt/eNOS pathway, unveiling a novel mechanism by which oestradiol regulates pathological cardiomyocyte growth after infarction.